2021
DOI: 10.1007/s12207-021-09435-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Negative Response Bias: a Review of the Noncredible Overreporting Scales of the MMPI-2-RF and MMPI-3

Abstract: The Minnesota Multiphasic Personality Inventory (MMPI) instruments have a rich history of the inclusion of embedded strategies to identify invalidating response styles-such as non-responding, inconsistent responding, and noncredible underreporting or overreporting of symptoms-and to identify the impact of such response styles on substantive test score conclusions and extra-test considerations. This paper briefly reviews that history before focusing on the scales that detect overreported psychopathology, somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The main purpose of PVTs is to assess excessively poor performance on cognitive tests (underperforming on cognitive tasks), which is often done with the Reliable Digit Span of the Wechsler Adult Intelligence Scale (e.g., Babikian et al, 2006), the Test of Memory Malingering (Tombaugh, 1996), and/or other similar tools. The primary purpose of SVTs is to assess negative response bias on symptom scales (overreporting of experienced psychological problems), which is often done using the validity scales of the Minnesota Multiphasic Personality Inventory (MMPI) instruments (see Burchett & Bagby, 2022), the Structured Inventory of Malingered Symptomatology (SIMS; Smith & Burger, 1997), and/or other similar measures. Ideally, professionals assessing the credibility of alleged mental health problems should include multiple independent SVTs and multiple independent PVTs in their assessment batteries (Gancedo et al, 2021a; Sweet et al, 2021).…”
Section: The Current Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of PVTs is to assess excessively poor performance on cognitive tests (underperforming on cognitive tasks), which is often done with the Reliable Digit Span of the Wechsler Adult Intelligence Scale (e.g., Babikian et al, 2006), the Test of Memory Malingering (Tombaugh, 1996), and/or other similar tools. The primary purpose of SVTs is to assess negative response bias on symptom scales (overreporting of experienced psychological problems), which is often done using the validity scales of the Minnesota Multiphasic Personality Inventory (MMPI) instruments (see Burchett & Bagby, 2022), the Structured Inventory of Malingered Symptomatology (SIMS; Smith & Burger, 1997), and/or other similar measures. Ideally, professionals assessing the credibility of alleged mental health problems should include multiple independent SVTs and multiple independent PVTs in their assessment batteries (Gancedo et al, 2021a; Sweet et al, 2021).…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…Compared to the large and growing number of published PVTs, there are still relatively few validated SVTs available to professionals (Pina et al, 2022; Sherman et al, 2020; Sweet et al, 2021). The most widely used and probably most empirically sound negative response bias indices are the validity scales of the MMPI instruments (Burchett & Bagby, 2022; Giromini et al, 2022). However, administering the MMPI requires a nonnegligible amount of time and noticeable cognitive effort on the part of the person being assessed, so that administering additional and independent SVTs alongside the MMPI instruments may not always be feasible.…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…In addition, some minor wording changes were also made to simplify existing items. The first article in this Special Issue focuses on the validity scales of the MMPI-2-RF and MMPI-3 (Burchett & Bagby, 2021).…”
Section: The Validity Scales Of the Mmpi-2-rf And Mmpi-3mentioning
confidence: 99%
“…The amount of empirical research supporting the effectiveness of the validity scales of the MMPI-2-RF is impressive, and studies contributing to the validity of their MMPI-3 counterparts are also rapidly accumulating. Based on their review of the relevant literature, Burchett and Bagby (2021) conclude that the Fp-r is by far the most effective MMPI-2-RF validity scale for capturing overreporting of various types of mental health problems, with a cut score ≥ 100 T maximizing the balance between overall hit rates and specificity. Indeed, the Fp-r has shown the most satisfactory classification accuracy not only in detecting feigned emotional disturbance, but also in detecting feigned cognitive impairment.…”
Section: The Validity Scales Of the Mmpi-2-rf And Mmpi-3mentioning
confidence: 99%
“…Notably, higher RBS scores have been associated with more subjective memory complaints but not with objective memory test performance (Gervais et al, 2008(Gervais et al, , 2010. The RBS has been shown to be highly sensitive for cognitive symptom validity across civilian (forensic and clinical), military, and veteran populations (Burchett & Bagby, 2022;Grossi et al, 2017;Jones et al, 2012;Jones & Ingram, 2011; N. W. Nelson et al, 2007;Sharf et al, 2017;Whitney et al, 2008;Wygant et al, 2010;Young et al, 2011), as well as shown clinical utility in a seizure disorder sample . Given the emphasis of the present study on detecting cognitive symptom invalidity and that other MMPI-2-RF validity indicators either assess noncognitive symptom invalidity (e.g., Fp-r assessing psychopathology symptom invalidity) or assess multiple types of symptom invalidity (e.g., FBS-r assessing both cognitive and somatic symptom invalidity), only the RBS scale was used in the present study.…”
Section: Examinee-completed Symptom Validity Testsmentioning
confidence: 98%